Pengendalian Kualitas Pada Proses Thread Rolling Menggunakan Metode Plan Do Check Action (Pdca) Dan Qc Seven Tools - Slevin Lintang Bimasakti; Mukhlisin; Sutrisno Aji Prasetyo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
PT. Saga Hikari Teknindo Sejati is a fastener manufacturing company that frequently faces high claims for bolt thread damage, particularly thread misalignment defects during the threading process. This research aims to reduce claims using the QC Seven Tools, PDCA (Plan, Do, Check, Action) method, and 5W+1H. The research focuses on analyzing the most frequent claim cases from the past six months. Root cause analysis using the cause-and-effect diagram identified thread misalignment as the primary issue. Improvement measures were implemented and monitored using quality indicators, resulting in a 50% reduction in thread damage claims and a 10% increase in production efficiency. The study concludes that the PDCA and QC Seven Tools methods are effective in minimizing damage claims and enhancing production efficiency. It is recommended that the company continue applying this method and integrate it with similar rolling machines